Characterisation of Dalmarnock Fire Test One - Abecassis Empis, Cecilia; Reszka, Pedro; Steinhaus, Thomas; Cowlard, Adam; Biteau, Hubert; Welch, Stephen; Rein, Guillermo; Torero, Jose L (Elsevier, Journal Experimental Thermal and Fluid Science, 2008)
The Dalmarnock Tests comprise a set of fire experiments conducted in a real high-rise building in July 2006. The two main tests took place in identical flats, Test One allowing the fire to develop freely to post-flashover conditions while Test Two incorporated sensor-informed ventilation management. The test compartments were furnished with regular living room/office items and fully instrumented with high sensor densities. The furniture and objects acting as fuel were arranged to provide conditions that favour repeatability. A full description of the set up of the tests, including fire monitoring sensors, is provided. Focus is on the larger Test One fire for which the major events are reported together with a thorough characterisation of the fire using sensor information. The main aim of the experiments was to collect a comprehensive set of data from a realistic fire scenario that had a resolution compatible with the output of field models. The characterisation of Test One provides a platform with potential for analytical and computational fire model validation.
Journal paper
Keywords: Fire Test; Experiment; Firergrid; Glasgow; high rise